Sniper Bot - Dr.G. Seshikala, Krishna Kumar, Ajay Raj.K, Neeraj Roshan , Shashank.S (International Journal of Advanced Science and Technology, 2020)
The proposed project is a minimized version of a military tank with advanced features such as facial recognition and a camera. The sniper is used to take down targets from a distance. Additionally, a drone with camera has been added for aerial surveillance and to get a clear view of the field in which it is deployed. The project is only meant to be carried for only special missions as the project could be lethal in any case. Also, the project comprises of additional features like radar using ultrasonic sensor and a metal detector for the bot's security.The Sniper Bot robot system has a modular design incorporating a various sensor package. It is quick, tough and easy to use. This robot prototype has a decent amount of payload-to-weight ratio and can be deployed in all environmental and in any terrain conditions.